Simulação hidrossedimentológica com o modelo LISEM em uma pequena bacia hidrográfica rural - Dalbianco, Leandro (2013)
Hydrossedimentological monitoring and modeling have been used as important tools to evaluate and simulate the hydrosedimentological processes in rural watersheds, in order to effectively propose conservation practices in environmentally sensitive locations. The objective of this research was to evaluate the performance of a physically based hydrological model (LISEM - Limburg Soil Erosion Model) in quantifying runoff and erosion in a rural catchment with high spatial variability (horizontally and vertically) physical and hydrological characteristics of the soil. The catchment has an area of 1.19 km2 and is situated in the northeastern region of the Rio Grande do Sul state, Brazil. Soils are characterized by reduction of water flow in the vertical soil profile either by the small thickness (Entisols and Inceptisols) or textural gradient between horizons (Ultisols) - and are associated with variations of relief, which is composed of soft hills in the top section and mountainous in the bottom section of the catchment. The predominant land use is tobacco farming (Nicotiana tabacum L.), where the surface layer of the soil is tilled to form ridges. In the first stage of the study, five slopes of the basin used for tobacco cultivation were sampled to characterize the physical and hydraulic properties at different points in the relief (top, middle slope and lowland) and four soil layers (0.00 to 0.04, from 0.20 to 0.24, from 0.40 to 0.44 and from 0.60 to 0,64 m). Field trials were also conducted to determine the infiltration rate on the slopes, and equations were also established to estimate the saturated hydraulic conductivity in each layer of soil sampled. In the second step, the LISEM model was calibrated to represent the hydrograph and sedimentograph of 20 rainfall events monitored in the river mouth from 2009 to 2012. The results of the first stage show that there is horizontal and vertical variability of physical and hydraulic properties on the slopes, being that the hillsides have a higher saturated hydraulic conductivity due to its coarser texture. Both the hydraulic conductivity and the infiltration rate were effective in identifying the horizontal variability of water flow on the slopes. The hydraulic conductivity can be estimated with good accuracy when variables from subsoil layers, for example, the total sand content, are used. The results of the second stage of the study revealed that the LISEM had a good performance in modeling the hydrograph. However, it was not possible to represent the sedimentograph, and there was an overestimate in sediment production. The model s equations related to erosion do not represent the dynamics that occur in this catchment.